2016
DOI: 10.1080/10503307.2015.1136443
|View full text |Cite
|
Sign up to set email alerts
|

Setbacks in the process of assimilation of problematic experiences in two cases of emotion-focused therapy for depression

Abstract: As in previously studied therapies, setbacks in EFT, usually represent productive work on relatively less advanced strands of the client's major problems. Results point to the importance of the therapist attending to the limits of the client's therapeutic ZPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 64 publications
7
20
0
8
Order By: Relevance
“…BDI-II, OQ-45) in the cases of Julia and Afonso is also consistent with results of previous assimilation studies (e.g., Mendes et al, 2015;see Stiles, 2002). Like other unimproved cases, reported in the assimilation literature, (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…BDI-II, OQ-45) in the cases of Julia and Afonso is also consistent with results of previous assimilation studies (e.g., Mendes et al, 2015;see Stiles, 2002). Like other unimproved cases, reported in the assimilation literature, (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Consistently with previous assimilation model studies of therapist interventions (Caro-Gabalda, et al, 2015;Meystre, et al, 2013;Meystre, et al, 2015), this study showed how the therapist interventions seemed to be responsive to these two client's emergent needs and capacities, facilitating the assimilation of their problematic experiences, by taking into account their current TZPD. The therapists' choices of whether to support or challenge seem to reflect each client's emergent needs.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A series of intensive case studies of assimilation progress in different therapeutic models has shown that good outcome clients, as assessed by standard symptom intensity measures, progress toward high APES levels across their sessions (e.g., Brinegar, Salvi, & Stiles, 2008;Caro Gabalda, 2011;Caro Gabalda, Stiles, & Pérez Ruiz, 2016;Gray & Stiles, 2011;Honos-Webb, Stiles, & Greenberg, 2003;Knobloch, Endres, Stiles, & Silberschatz, 2001;Mendes et al, 2016;Osatuke et al, 2007;Ribeiro, Braga et al, 2016a;Ribeiro, Cunha et al, 2016b). For example, in a study of one good outcome client, Basto et al (2016) found a strong negative correlation across 16 sessions of CBT between APES level and symptom intensity.…”
Section: Relation Of Assimilation To Therapy Outcomementioning
confidence: 99%